2017
DOI: 10.9787/pbb.2017.5.4.282
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of the Dehydrin Genes in the Cucurbitaceae Species

Abstract: This is an Open-Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/by-nc/4.0) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited. ABSTRACT Dehydrins (DHNs) are hydrophilic proteins with conserved lysine-rich K-segment, which belong to Group II of the late embryogenesis abundant (LEA) protein family. DHNs are considered as molecular chaper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Putative DHN coding genes containing the characteristic 'K' peptide motif of dehydrins (Close, 1996) were selected in silico from the cucumber genome. These corresponded to cucumber dehydrins reported earlier by Lee et al (2017) and Zhou et al (2018) (Table 3). Some experimental data already supported a predicted role of this gene family in stress responses of cucumber.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Putative DHN coding genes containing the characteristic 'K' peptide motif of dehydrins (Close, 1996) were selected in silico from the cucumber genome. These corresponded to cucumber dehydrins reported earlier by Lee et al (2017) and Zhou et al (2018) (Table 3). Some experimental data already supported a predicted role of this gene family in stress responses of cucumber.…”
Section: Discussionsupporting
confidence: 88%
“…We do not believe that basal expression could be triggered by occasional cold exposure, as we grew the plants at a constant high temperature (26°C) specifically for this reason. Earlier observations already suggested SKn and YnSKn type dehydrins exhibiting higher, and lower level of expression, respectively, in the absence of stress (Lee et al, 2017). Stress independent expression of DHNs was also shown in other plant species in several previous studies (Deák et al, 2017;Natali et al, 2007).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The transcriptome data has also enabled genome-wide studies of individual salt responsive genes as well as their functions. For example, Kumar et al [ 21 ] reported that the ectopic expression of OsSta2 gene in rice enhanced salt tolerance, while AP2/EREBP and dehydrin genes have been characterized in Cucurbitaceae species [ 22 , 23 ]. Also, the transcriptome of plants growing under other abiotic stresses such as cold [ 24 , 25 ], drought [ 26 , 27 , 28 , 29 ], and heat [ 30 ] have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…These genes play important roles in dealing with various environmental stresses. Further genome-wide identification provided in the Cucurbitaceae species was focused on the dehydrin genes encoding dehydrines—hydrophilic proteins act like molecular chaperons playing crucial role in the process of abiotic stress tolerance [ 45 ]. Both of these studies could be essential for future breeding of new Cucurbitaceae cultivars with stress tolerance.…”
Section: Stress Responsementioning
confidence: 99%